The analysis of traditional Malay song (Asli) Case study: Patah hati / Nor Fathin Ayu Ahmad Termuzi - Ahmad Termuzi, Nor Fathin Ayu (2012)
This thesis which is about Malay traditional music is a study related to the course taken by the researchers of the field of composition. It is a transcription and the analysis of the study, idiom (patah lenggok) which was found in the native Malay singing. The objective of this study was to standardize traditional vocal learning in line with the western vocal educational standard. It also aims to preserve the treasures of this hereditary. With this study, we will have this treasure remain and preserved until any time. The background of this study is concerned with the analysis of the idiom (patah lenggok) melodies and Malay songs "asli". It requires listening as each song is written from the idioms (patah lenggok) singers own variations. Researchers have been using equipment and gadget such as mobile phones, laptops, and stationery such as books and organizers. Among the music software, the researcher has used the Sibelius notation software and other software such as Microsoft words.